2023
DOI: 10.1111/aogs.14623
|View full text |Cite
|
Sign up to set email alerts
|

Fetal electrocardiography and artificial intelligence for prenatal detection of congenital heart disease

Abstract: IntroductionThis study aims to investigate non‐invasive electrocardiography as a method for the detection of congenital heart disease (CHD) with the help of artificial intelligence.Material and methodsAn artificial neural network was trained for the identification of CHD using non‐invasively obtained fetal electrocardiograms. With the help of a Bayesian updating rule, multiple electrocardiographs were used to increase the algorithm's performance.ResultsUsing 122 measurements containing 65 healthy and 57 CHD ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A recent article has discussed screening for cardiovascular disease in women using AI [ 259 ], this being a subcategory analyzed by the authors within the wide range of areas in which AI has proven effective in screening (e.g., congenital disease screening from both ECG analysis [ 90 ] to heart sound analysis [ 91 ] and fetal ultrasound [ 93 ], screening for reduced fraction heart failure [ 109 ], screening for hypertension [ 138 ], screening for valvular disease [ 218 , 219 , 220 , 222 , 227 , 228 ], and screening for rare diseases such as Fabry disease [ 60 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent article has discussed screening for cardiovascular disease in women using AI [ 259 ], this being a subcategory analyzed by the authors within the wide range of areas in which AI has proven effective in screening (e.g., congenital disease screening from both ECG analysis [ 90 ] to heart sound analysis [ 91 ] and fetal ultrasound [ 93 ], screening for reduced fraction heart failure [ 109 ], screening for hypertension [ 138 ], screening for valvular disease [ 218 , 219 , 220 , 222 , 227 , 228 ], and screening for rare diseases such as Fabry disease [ 60 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the use of AI could improve the quality of patient care, help optimize the treatment of these patients, extend life expectancy, save time for the attending physician, and reduce healthcare costs [ 243 ]. Artificial intelligence has found usefulness in current studies in the prediction of cardiovascular events in adults operated on for Fallot tetralogy [ 89 ] and the screening of congenital diseases based on ECG [ 90 ] based on cardiac auscultation [ 91 ] or echocardiography [ 93 , 94 ]. De Vries R.I. et al conducted a study that developed an ECG-based fetal screening method for CHD.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has consistently demonstrated improvements in sensitivity and specificity when detecting various Congenital Heart Diseases-(CHD) early in pregnancy. These findings hold the potential to enable earlier diagnosis of fetal cardiac conditions, offering a broader timeframe for implementing interventions that can ultimately reduce mortality rates and lower associated risks (11)(12)(13).…”
Section: Prenatal Screeningmentioning
confidence: 99%
“…More recently, the group from Children’s National described a new frequency-based technique for attenuating the maternal ECG to enhance and extract the fECG [ 118 ]. Ongoing efforts utilize artificial intelligence, including artificial neural networks and deep learning models, to detect fetal arrhythmias [ 119 , 120 , 121 , 122 ].…”
Section: Diagnostic Toolsmentioning
confidence: 99%